The language of food : through the lens of East Asian films and drama - Kiaer, Jieun; Kim, Loli; Calway, Niamh (Abingdon, Oxon ; New York, NY : Routledge, 2025)
"The Language of Food: Through the Lens of East Asian Films and Drama invites readers into the fascinating world where food culture and language intersect, revealing how each dish communicates beyond mere taste. Through East Asian films and television shows, this book uncovers the rich tapestry of 'food languages' embedded within East Asian cultures. Divided into three parts-Base, Ingredients, and Seasoning-this book provides a structured exploration of this phenomenon. The Base section offers philosophical and historical context, while the Ingredients section delves deeper into specific themes, using film examples to illustrate the nuanced communication inherent in food culture. Finally, the book is 'seasoned' with linguistic insights and a practical food words glossary, aiding readers in navigating the intricate verbal and cultural nuances at play. This illuminating resource goes beyond the realm of food itself, offering a profound understanding of how each dish carries its language, enriching communication and deepening cultural connections. This book will captivate students and researchers of East Asian languages, media studies, film studies, Korean Wave studies, and anyone intrigued by the intricate relationship between food and language"--
Keywords: Motion pictures -- East Asia -- History; Oriental drama -- History and criticism; Food in motion pictures; Food -- Social aspects -- Asia; Language and culture -- East Asia; FOREIGN LANGUAGE STUDY / Korean; FOREIGN LANGUAGE STUDY / Japanese; COOKING / General